Protocol for stage 2 of the GaP study (genetic testing acceptability for Paget's disease of bone): A questionnaire study to investigate whether relatives of people with Paget's disease would accept genetic testing and preventive treatment if they were available - McCallum Marilyn; Weinman John; MacLennan Graeme; Marteau Theresa; Entwistle Vikki A; Campbell Marion K; Robertson Clare; Francis Jill; Johnston Marie; Langston Anne L; Miedzybrodska Zosia; Charnock Keith; et al. (BMC, 2008)
Abstract Background Paget's disease of bone (PDB) disrupts normal bone architecture and causes pain, deformity, deafness, osteoarthritis, and fractures. Genetic factors play a role in PDB and genetic tests are now conducted for research purposes. It is thus timely to investigate the potential for a clinical programme of genetic testing and preventative treatment for people who have a family history of PDB. This study examines the beliefs of relatives of people with PDB. It focuses particularly on illness and treatment representations as predictors of the acceptability and uptake of potential clinical programmes. Illness representations are examined using Leventhal's Common Sense Self-Regulation Model while cognitions about treatment behaviours (acceptance of testing and treatment uptake) are conceptualised within the Theory of Planned Behaviour. Methods/Design A postal questionnaire of non-affected relatives of people with Paget's disease. The sample will include relatives of Paget's patients with a family history of Paget's disease and relatives of Paget's patients without a family history of Paget's disease. The questionnaire will explore whether a range of factors relate to acceptability of a programme of genetic testing and preventive treatment in relatives of Paget's disease sufferers. The questionnaire will include several measures: illness representations (as measured by the Brief Illness Perceptions Questionnaire); treatment representations (as measured by Theory of Planned Behaviour-based question items, informed by a prior interview elicitation study); descriptive and demographic details; and questions exploring family environment and beliefs of other important people. Data will also be collected from family members who have been diagnosed with Paget's disease to describe the disease presentation and its distribution within a family. Discussion The answers to these measures will inform the feasibility of a programme of genetic testing and preventive treatment for individuals who are at a high risk of developing Paget's disease because they carry an appropriate genetic mutation. They will also contribute to theoretical and empirical approaches to predicting diagnostic and treatment behaviours from the combined theoretical models.